Factors associated with the occurrence and persistence of subthreshold and full attention-deficit hyperactivity disorder in women: A population-based epidemiological study - Ana Buadze; Vladeta Ajdacic-Gross; Mario Müller; Yanhua Xu; Erich Seifritz; En-Young N. Wagner; Roland von Känel; Jennifer Glaus; Setareh Ranjbar; Enrique Castelao; Marie-Pierre F. Strippoli; Martin Preisig; et al. (PLoS ONE, 2026)
Background Attention-deficit hyperactivity disorder (ADHD) is one of the most frequent neurodevelopmental disorders in youth, and persists into adulthood in the majority of cases. Our objective was to examine which factors are associated with ADHD in women across different disorder levels (subthreshold, full, persistent). Methods Analyses were carried out using data from the CoLaus|PsyCoLaus study (N = 2741, age range 35–88 years). The factors of interest comprised familial aggregation, age of ADHD onset, somatic comorbidity, adverse childhood experiences and trauma, parental bonding, as well as immunological and cardio-metabolic markers. Association analyses were combined with a person-centered analysis approach (latent class/ latent profile analysis (LCA/ LPA)). Results Subthreshold and full ADHD both comprised higher levels of adverse childhood experiences and lower scores of parental bonding. Familial aggregation and earlier age of onset were prominent features in full ADHD, but less relevant regarding persistence. There, increased levels of immunological and cardiometabolic markers played the major role (monocytes, neutrophils, hsCRP, insulin and leptin). In a subgroup perspective, adverse childhood experiences were the most prominent feature of the “burdened” opposed to the “idiopathic” LCA/LPA subgroup. The “burdened” subgroup showed higher persistence rates than the “idiopathic” subgroup in subthreshold and full ADHD. Conclusions The full picture of subthreshold, full and persistent ADHD in women was characterized by surprisingly heterogeneous association patterns. The heterogeneity does not only rely on severity levels but is primarily associated with additional factors, including familial aggregation in full ADHD or proinflammatory immune and cardiovascular system dysregulation in persistent ADHD.